Upward flame spread and self‐induced buoyant blow‐off over two‐sided thin fabric at different inclination angles. (12th August 2021) - Gao, Yunji; Yang, Xiaolong; Luo, Yueyang; Guo, Feng; Zhang, Yuchun; Gong, Liang
Summary: A series of upward flame spread experiments over two‐sided long thin flax fabric sheets were conducted at different inclination angles from horizontal (0°) to vertical (90°). With the inclination increased to a critical angle, the flame on the lower side of the 4 and 6 cm wide samples can be blown off spontaneously. After the lower‐side blow‐off, the remained flame on the upper side spread steadily to the end of the sample. To clarify the controlling mechanism, the flame spread rates and flame geometry characteristics were investigated and compared in different inclination angles. The maximum flame spread rate and flame length monotonically increased with the inclination angle under the assistance of self‐induced buoyancy. However, the steady flame spread rate and flame length on the remained side dropped significantly after one‐side extinction. The lower side flame was blown off by the large buoyant flow velocity induced from the critical flame length, which is controlled by the small Damköhler number. Flame thickness and flame tilt angle were analyzed at varied inclinations to help understand the heat transfer from the flame to the unburnt fuel surface. Two opposite effects of self‐induced buoyancy were proposed at different ranges of inclination: the thermal assistance regime at the lower inclination angle and the kinetical extinguishing regime at a higher inclination angle. They are dominated by the heat transfer from the flame and local fluid dynamic around the flame base, respectively.